Design and the vernacular : interpretations for contemporary architectural practice and theory - Memmott, Paul; Ting, John H. S.; O'Rourke, Tim (Timothy Charles); Vellinga, Marcel (2023)
"Design and the Vernacular explores the intersection between vernacular architecture, local cultures, and modernity and globalization. Focussing on the vast and diverse global region of Australasia and Oceania, it examines the relevance and role of vernacular architecture to contemporary urban planning and architectural design, placing this against a contextual background of rapid political, economic, technological, social and environmental changes including globalization, exchanges of people, finance, material culture, and digital technologies. Sixteen chapters by architects designers and theorists, including Indigenous writers, explore key questions about the agency of vernacular architecture in shaping contemporary building and design practice. These questions include: How have Indigenous and First Nations building traditions shaped modern building practices? What can the study of vernacular architecture contribute to debates about sustainable development? And how has vernacular architecture been used to argue for postcolonial modernisation and nation-building and what has been the effect on heritage and conservation? Such questions provide valuable case studies and lessons for architecture in other global regions -- and challenge assumptions about vernacular architecture being anachronistic and static, instead demonstrating how it can shape contemporary architecture, nation building and cultural identities"--
The Architectural Vernacularisation of Pacific Aid Practice / Charmaine 'Ilaiū Talei -- Adaptive Uses of Traditional Windbreaks and Bough Shades for Indigenous Housing in Australia / Timothy O'Rourke -- Translating Spaces: Speculative Landscape Futures for New Climate Diasporas / Lizzie Yarina, Penny Allan and Martin Bryant -- Appropriating the Native: Shifting Definitions of the Vernacular in Twentieth-Century Philippine Architecture / Edson G. Cabalfin.
Includes bibliographical references and index.
Keywords: Vernacular architecture -- Australasia; Architecture and society -- Australasia; Vernacular architecture -- Southeast Asia; Architecture and society -- Southeast Asia